Audiovisual Media Development for Conceptual Understanding in Elementary Science Education: An ADDIE Model Study - Anazwa Khairani Dalimunthe; Andina Halimsyah Rambe (Journal of Social Work and Science Education, 2027)
Conceptual understanding is a fundamental cognitive skill in elementary science education, yet many students struggle with abstract concepts such as the human digestive system, which involves invisible internal processes. This study aimed to develop and evaluate audiovisual media to enhance conceptual understanding of the human digestive system among fifth-grade elementary school students. Employing a Research and Development (R&D) methodology with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study involved 17 fifth-grade students from SD Negeri 101770 Tembung. Data were collected through expert-validation questionnaires, teacher and student response questionnaires, classroom observation, interviews, and pretest-posttest conceptual-understanding assessments. Validity assessments from the media expert (91.67%) and material expert (98.75%) categorized the media as highly feasible. Practicality testing yielded 96.67% from the teacher response and 84.12% from student responses, both within the highly feasible category. The mean conceptual-understanding score increased from 35 on the pretest to 93 on the posttest, producing an N-gain of 0.89 (89%), categorized as high. The audiovisual media visualized the sequence of digestive processes through synchronized visual and verbal representations, thereby helping students engage with processes that could not be observed directly. These findings indicate high validity, practicality, and potential effectiveness within the one-group trial. The study contributes an ADDIE-based example of how audiovisual media can make abstract elementary science content more concrete. Future studies should test the media with larger and more diverse samples, additional science topics, and controlled experimental designs.